In silico identification and characterization of miRNA in tursiops truncatus - KHALIDA NAVEED; AYESHA GUL; SYEDA TATHEER FATIMA (International Journal of Pharma and Bio Sciences, 2016)
MicroRNAs (miRNAs) belong to class of single-stranded RNA molecules having length of 22 nucleotides. They take part in regulation of gene expression in numerous organisms at post-transcriptional repression level of messenger RNA. In the current research, the EST databases of Tursiops truncatus were explored for the prediction and analysis of potential miRNAs and their target genes with the aid of various computational and bioinformatics tools. In Tursiops truncates, the identification of miRNAs and their targets were carried out on linux operating system featured with Standalone BLAST, CD-Hit, Clustalw, RNAhybrid and imiRNA-SSF. Initially 24 potential miRNAs were identified among them two of them are paralogous with 100% identity. These 24 miRNAs were subjected for analysis of paralogous sequences, secondary structures, true and pseudo miRNAs and phylogenetic studies using CD-HIT, RNAhybrid, imiRNA-SSF, clustalw tools respectively. Finally 2 miRNA with id ttr- mir-147 and ttr- miR-4680 were predicted as mature and real miRNA.The present study suggested that there is an sample of miRNAs in this specie playing some crucial role in the development and physiology of Tursiops truncatus and can further explored for functional studies. These predicted miRNAs will be helpful to accelerate the pace miRNA discovery that eventually lead to an improved and better understanding of miRNA role in the course of development and physiology of Tursiops truncatus.